Assessment of Knowledge, Attitude and Practices of Health Workers Towards Hepatitis B Virus Infection Prevention in Health Centers of Bushenyi District. - Byamukama, Julius (Kabale University, 2024)
Hepatitis B virus (HBV) infection in the health setting is a global public health problem. The risk of occupational exposure to HBV among healthcare workers is a major concern, especially among students in health professions and health workers in health centers. In Uganda Bushenyi district, very little is known about the knowledge, attitude, and practices (KAP) of health workers in the health centers towards Hepatitis B virus prevention. Thus, the purpose of this study. Assessment of Knowledge, Attitude, and Practices of health workers in the health centers towards Hepatitis B virus infection prevention. A cross-sectional study technique was used from April 2018 to June 2018 and a total of 246 healthcare professionals from health centers of Bushenyi district were included in the study using a systematic random sampling technique. Data were collected using a self-administered structured questionnaire and analyzed by using SPSS version 20, which presented tables and charts in this report. The majority of the study participants, (>80 %) had a piece of adequate knowledge of risk factors for HBV, its mode of transmission, and prevention. 83.3 % of participants had a positive attitude. following infection control guidelines, and 201 (81.7 %) respondents believe that all healthcare workers should take the HBV vaccine. However, only 5 (2 %) health workers had completed the three doses schedule of HBV vaccination. Whereas, a significant number of health workers, 66 (26.8 %), had been exposed to blood/body fluid through needle stick injuries at least once since they started their duties in the health facility. Despite the wide professional background of the study, my results showed that overall knowledge regarding HBV prevention, and its mode of transmission was high at (86.2 %). Most respondents knew that exposure to infected blood or body fluid, contaminated needles, contact with non-intact skin, or unsafe sexual contacts were risk factors for HBV infection. This finding was consistent with the previous study from Cameroon that reported a good knowledge of the study participants on HBV infection. However, it was higher than the 56.2 % knowledge levels at Haramaya University Ethiopia, 59 % from Iraq, and 14.5 % from Lao DPR. Nevertheless, I found that a relatively lower proportion of health workers knew that HBV has treatments (52.4 %) and post-exposure prophylaxis (67.1 %). This indicates that there is a need to alleviate the gaps as these might affect behaviors in seeking medical attention. In conclusion, my study found that health workers are at a very high risk of contracting HBV infection during their training owing to the low HBV vaccine uptake rate and high rate of accidental exposure to blood. Thus, we recommend that all health workers in the health centers should be vaccinated before they enter into health professional practices.